SmFeO3 and SmFe1‐xErxO3 based perovskite nanorods for improved oxygen and hydrogen evolution functions. (1st December 2020) - Ilanchezhiyan, P.; Mohan Kumar, G.; Siva, C.; Kang, T.W.; Kim, D.Y.
Summary: Samarium (Sm) based perovskite nanorod‐like structures were processed for electrocatalytic functions involving oxygen and hydrogen evolution reactions. Influence of erbium (Er) ions on the structural and electrocatalytic properties of SmFe1−x Erx O3 perovskites were studied under varied alkaline pH (8.5‐14) conditions. The rod‐like dimensional analysis was obtained through scanning/transmission electron microscopes. Diffraction signals affirmed the presence of samarium oxide (Sm2 O3 ) traces in processed perovskites. X‐ray photoelectron spectroscopy data signified the presence of corresponding oxides and determined the valence state of Sm, Er and Fe ions. Er ions were found to boost the production of oxygen and hydrogen molecules. The anodic overpotential values improved from 216 mV to 184 mV, while cathodic overpotential values improved from 231 mV to 213 mV upon Er inclusion. Electrocatalytic results approved SmFe1−x Erx O3 as a promising oxygen/hydrogen liberating electrocatalyst with remarkable stability and Tafel slopes that improved from 96 to 77 mV/dec and 78 to 55 mV/dec upon Er incorporation in host perovskite. Abstract : SmFe1‐x Erx O3 rare earth perovskite metal oxides with improved conductivity facilitates the efficient interaction of charge carriers to create additional catalytic sites for improved OER/HER performance.